The PHD domain is required to link Drosophila Pygopus to Legless/beta-catenin and not to histone H3. - Kessler, R.; Hausmann, G.; Basler, K. (Mechanisms of Development, 2009)
In Drosophila Pygopus (Pygo) and Legless (Lgs)/BCL9 are integral components of the nuclear Wnt/Wg signaling machine. Despite intense research, ideas that account for their mode of action remain speculative. One proposition, based on a recently discovered function of PHD fingers, is that Pygo, through its PHD, may decipher the histone code. We found that human, but not Drosophila, Pygo robustly interacts with a histone-H3 peptide methylated at lysine-4. The different binding behavior is due to a single amino acid change that appears unique to Drosophilidae Pygo proteins. Rescue experiments with predicted histone binding mutants showed that in Drosophila the ability to bind histones is not essential. Further experiments with Pygo-Lgs fusions instead demonstrated that the crucial role of the PHD is to provide an interaction motif to bind Lgs. Our results reveal an interesting evolutionary dichotomy in Pygo structure-function, as well as evidence underpinning the chain of adaptors model.